Ropivacaine inhibits the proliferation and migration of colorectal cancer cells through ITGB1. Issue 1 (1st January 2021) - Wang, Xiao; Li, Tianzuo
ABSTRACT: To study whether ropivacaine inhibits the proliferation and migration of colon cancer cells through ITGB1 (Integrin beta-1). First, the effect of ropivacaine on cell proliferation and migration was detected by MTT and Transwell. DAPI staining, annexin V staining and Western blot were used to detect the expression of apoptosis-related proteins to investigate the effect of ropivacaine on cell apoptosis. Using bioinformatics software to predict the potential drug targets of ropivacaine. RT-PCR, Western blot and immunofluorescence verify the distribution and expression of the drug target ITGB1, and detect its downstream-related proteins to further prove that ropivacaine affects colon cancer cells by acting on ITGB1 protein. 1. Ropivacaine significantly inhibited the proliferation of colon cancer cells and promoted their apoptosis 2. Ropivacaine could interact with ITGB1 protein, and inhibited the expression of ITGB1 protein in colon cancer cells, thereby affecting its downstream signaling pathway. Ropivacaine regulates the function of colon cancer cells by targeting the expression of ITGB1 protein and affecting the activation of its downstream signaling pathways. Abbreviation: Integrin beta-1 (ITGB1); 3-(45)-dimethylthiahiazo (-z-y1)-35-di- phenytetrazoliumromide (MTT); 4. 6-diamimo-2-phenyl indole (DAPI); Reverse transcrption PCR (RT-PCR); Colorectal cancer (CRC); Local anesthetics (LA); voltage-gated sodium channel (VGSC); dulbecco s modifed eade medium (DMEM); propidium iodide (PI); dodecyl sulf ate, sodium salt-Polyacrylamide gel electrophoresis (SDS-PAGE); Polyvinylidene Fluoride (PVDF); BCL2 associated X (Bax); Focal Adhesion Kinase (FAK); extracellular signal-regulated kmase (ERK); alpha serme threcnime-proteim kinase (AKT); Glyceraldehyde-3-phosphate dehydrogenase (GAPDH); Tris-buffered salme with 0.1% Tween 20 (TBST); Similarty ensemble approach (SEA) Graphical abstract: uf0001